In vivo evaluation of integrin αvβ6-targeting peptide in NSCLC and brain metastasis - Fan, Di; Zhang, Chengkai; Luo, Qi; Li, Baowang; Ai, Lin; Li, Deling; Jia, Wang (Frontiers in Oncology, 2023)
Integrin αvβ6, which is upregulated in malignancies and remains absent or weak in normal tissue, is a promising target in molecular imaging therapeutics. In vivo imaging of integrin αvβ6 could therefore be valuable for early tumor detection and intraoperative guidance. In this study, integrin αvβ6-targeting probe G2-SFLAP3 was labeled with near-infrared (NIR) dye Cy5.5 or radioisotope 68Ga. The resulting probes were evaluated in integrin αvβ6-positive A549 and αvβ6-negative H1703 xenograft mice models. The cellar uptake of G2-SFLAP3-Cy5.5 was consistent with the expression of integrin αvβ6. Both subcutaneous and brain metastatic A549 tumors could be clearly visualized by NIR fluorescent imaging of G2-SFLAP3-Cy5.5. A549 tumors demonstrated the highest G2-SFLAP3-Cy5.5 accumulation at 4h post-injection (p.i.) and remain detectable at 84h p.i. The fluorescent signal of G2-SFLAP3-Cy5.5 was significantly reduced in H1703 and A549-blocking groups. Consistently, small-animal PET imaging showed tumor-specific accumulation of 68Ga-DOTA-G2-SFLAP3. Therefore, G2-SFLAP3 represents a promising agent for noninvasive imaging of non-small cell lung cancer (NSCLC) and brain metastases.